2018
DOI: 10.1159/000489703
|View full text |Cite
|
Sign up to set email alerts
|

National Trends in Emergency Room Visits of Dialysis Patients for Adverse Drug Reactions

Abstract: Background: Various medications are cleared by the kidneys, therefore patients with impaired renal function, especially dialysis patients are at risk for adverse drug events (ADEs). There are limited studies on ADEs in maintenance dialysis patients. Methods: We utilized a nationally representative database, the Nationwide Emergency Department Sample, from 2008 to 2013, to compare emergency department (ED) visits for dialysis and propensity matched non-dialysis patients. Log binomial regression was used to calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…In this issue of the American Journal of Nephrology , Chan et al [3] publish new insights into the magnitude of serious ADEs affecting patients on dialysis. The study examines 5 years’ worth of data from the Nationwide Emergency Department Sample (NEDS).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In this issue of the American Journal of Nephrology , Chan et al [3] publish new insights into the magnitude of serious ADEs affecting patients on dialysis. The study examines 5 years’ worth of data from the Nationwide Emergency Department Sample (NEDS).…”
mentioning
confidence: 99%
“…The NEDS database includes information on emergency department visits, hospital admissions, discharges to skilled nursing facilities, and in-hospital mortality, among other data elements [4]. For this study, dialysis status and diagnosis of ADE in the emergency department were identified by specific ICD-9 codes that are captured within the NEDS database [3]. …”
mentioning
confidence: 99%
See 3 more Smart Citations